2000
DOI: 10.1017/s0033822200053091
|View full text |Cite
|
Sign up to set email alerts
|

Some Comments on Accelerator Mass Spectrometry

Abstract: This paper discusses some aspects of the development of accelerator mass spectrometry (AMS), the international conferences that have been held, and the books that have been written on the subject. It also mentions some details of the technique and its strengths. Some of the interesting measurements that have been made recently are covered, and finally, it presents some thoughts on future developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The 10 B : 11 B and 6 Li : 7 Li ratios can theoretically be measured to better than 1% precision by measurement of multiple peaks of the Li 2 BO 2 z ion using ion counting detection. Bickle et al 344 found, however, that the relatively large Li z beam emitted simultaneously with the smaller Li 2 BO 2 z beam caused the Li remaining on the filament to fractionate.…”
Section: Analytical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 B : 11 B and 6 Li : 7 Li ratios can theoretically be measured to better than 1% precision by measurement of multiple peaks of the Li 2 BO 2 z ion using ion counting detection. Bickle et al 344 found, however, that the relatively large Li z beam emitted simultaneously with the smaller Li 2 BO 2 z beam caused the Li remaining on the filament to fractionate.…”
Section: Analytical Methodologymentioning
confidence: 99%
“…The 55-reference review by Kutschera 10 presented a broad view of the principles and potential of AMS in addition to selected applications. Other excellent general reviews were those of Gove, 11 which not only covered the historical development of AMS but also presented some thoughts on future developments, and of Hotchkis et al 12 on recent developments and the need for traceable RMs. The recent development of compact instruments for radiocarbon analysis using terminal voltages below 1 MV and ions in z1 or z2 charge states has been notable.…”
Section: Reviewsmentioning
confidence: 99%